2021
DOI: 10.1101/2021.01.25.428193
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antifungal effects of alantolactone onCandida albicans:anin vitrostudy

Abstract: The human fungal pathogen Candida albicans can cause many kinds of infections, including biofilm infections on medical devices, while the available antifungal drugs are limited to only a few. In this study, alantolactone (Ala) demonstrated antifungal activities against C. albicans, as well as other Candida species, with a MIC of 72 μg/mL. Ala could also inhibit the adhesion, yeast-to-hyphal transition, biofilm formation and development of C. albicans. The exopolysaccharide of biofilm matrix and extracellular p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The inhibition of the virulence factors of C. albicans by ALT was revealed just recently for the first time, and 18–72 µg/mL of ALT could exert disruptive effects on preformed biofilms, underlining the potential of these compounds. It is stated that the antifungal effects of ALT against C. albicans and several other Candida species may involve increased cell membrane permeability and ROS production [ 187 ]. Another recent study confirmed the antifungal properties of elecampane EO by indicating considerable inhibitory effects (MICs = 50–100 μg/mL) against C. albicans , C. glabrata , C. kruzey , C. parapsilosis , S. cerevisiae , and A. niger .…”
Section: Essential Oils From Selected Rootsmentioning
confidence: 99%
“…The inhibition of the virulence factors of C. albicans by ALT was revealed just recently for the first time, and 18–72 µg/mL of ALT could exert disruptive effects on preformed biofilms, underlining the potential of these compounds. It is stated that the antifungal effects of ALT against C. albicans and several other Candida species may involve increased cell membrane permeability and ROS production [ 187 ]. Another recent study confirmed the antifungal properties of elecampane EO by indicating considerable inhibitory effects (MICs = 50–100 μg/mL) against C. albicans , C. glabrata , C. kruzey , C. parapsilosis , S. cerevisiae , and A. niger .…”
Section: Essential Oils From Selected Rootsmentioning
confidence: 99%
“…Furthermore, Ala can inhibit the formation and development of C. albicans biofilms, which are responsible for catheter-related infections that are calcitrant to current antifungals. The mechanisms involve reactive oxygen species (ROS) overproduction and cell membrane damages (Liu et al, 2021). This was also indirectly confirmed by the latest report that the Ala-containing I. helenium root essential oil inhibits C. albicans growth, biofilm, phospholipase production, and germ-tube formation and that the cell membrane function was influenced by the essential oil (Stojanović-Radić et al, 2020).…”
Section: Antifungalmentioning
confidence: 61%